Ticks (Parasitiformes: Ixodida) on new world wild primates in Brazil. Issue 2 (17th February 2021) - Martins, Thiago F.; Teixeira, Rodrigo H. F.; Souza Jr, Julio C.; Luz, Hermes R.; Montenegro, Mônica M.; Jerusalinsky, Leandro; Bueno, Marina G.; Onofrio, Valeria C.; Amorim, Marinete; Gazêta, Gilberto S.; Da Silva, Paula De J.; Bitencourth, Karla; et al.
ABSTRACT: Brazil concentrates the largest number of primate species in the world. In the present study, an extensive literature review of ticks on New World wild monkeys has been carried out, demonstrating that between the years 1912 to 2018, 182 larvae, 137 nymphs and 31 adult ticks (10 males and 21 females) were collected on 78 primates (from 12 different species) in 28 distinct localities in the Brazilian territory. Additionally, examination of allotments of 11 tick collections of Brazil revealed that from 1919 to 2019, 93 larvae, 91 nymphs and 175 adult ticks (62 males and 113 females) were collected from 100 monkeys (among 20 different species) from 43 localities in distinct Brazilian biomes. Overall, 19 tick species were identified on wild primates in the country: Amblyomma aureolatum (Pallas, 1772), Amblyomma cajennense (Fabricius, 1787) sensu stricto, Amblyomma coelebs Neumann, 1899, Amblyomma dubitatum Neumann, 1899, Amblyomma geayi Neumann, 1899, Amblyomma incisum Neumann, 1906, Amblyomma longirostre (Koch, 1844), Amblyomma naponense (Packard, 1869), Amblyomma nodosum Neumann, 1899, Amblyomma ovale Koch, 1844, Amblyomma parkeri Fonseca & Aragão, 1952, Amblyomma romarioi Martins, Luz & Labruna, 2019, Amblyomma rotundatum Koch, 1844, Amblyomma sculptum Berlese, 1888, Haemaphysalis juxtakochi Cooley, 1946, Ixodes fuscipes Koch, 1844, Rhipicephalus microplus (Canestrini, 1888), Rhipicephalus sanguineus (Latreille, 1806) sensu lato, and Ornithodoros rostratus Aragão, 1911. The presence of A. incisum, A. naponense, A. nodosum, A. rotundatum and I. fuscipes on monkeys is recorded for the first time. Thisresearch is therefore a significant contribution to the knowledge of tick speciesassociated with non-human primates in the Neotropical region.